Pharmacokinetics of baicalin and oroxyloside in plasma and different tissues of rats after transnasal aerosol inhalation and intravenous injection of Tanreqing - Chen, Teng-Fei; Song, Ling; Gao, Yun-Hang; Li, Han; Li, Jian-Liang; Hou, Hong-Ping; Peng, Bo; Wang, Hui-Ying; Cheng, Wen-Hao; Ye, Zu-Guang; Li, Ying-Fei; Zhang, Guang-Ping (Frontiers in Pharmacology, 2022)
To avoid adverse drug reactions associated with injection, off-label nebulization of Tanreqing (TRQ) injection is often used in China to treat respiratory diseases. However, the aerodynamic properties and lung availability of TRQ aerosols remain largely uninvestigated. This study aimed to investigate the size distribution of TRQ aerosols, and to compare the pharmacokinetics and tissue distribution of two compounds from TRQ (baicalin and oroxyloside) after transnasal aerosol inhalation and intravenous administration. Furthermore, this study aimed to evaluate the efficacy of TRQ against lipopolysaccharide-induced lung inflammation. The Dv(50) and transmission of TRQ aerosols were 2.512 μm and 74.867%, respectively. The Cmax of baicalin and oroxyloside in rat plasma after inhalation was lower than that after intravenous injection. After inhalation, the area under the curve (AUC) of baicalin and oroxyloside in tissues (lung, bronchoalveolar lavage fluid, and trachea) were 7.9–115.3 and 9.5–16.0 times that observed after intravenous administration, respectively. Baicalin and oroxyloside maintained high concentrations 4 h after inhalation, but only 1 h after intravenous injection. The mean lung-to-plasma concentration ratios of baicalin and oroxyloside were 287.6 and 49.9 times higher than intravenous administration. Inhaled TRQ achieved the same effect against lipopolysaccharide-induced lung inflammation in mice at doses of only 1/16–1/8 of those administered intravenously. The results indicate that TRQ inhalation is a promising alternative to intravenous injections for the treatment of respiratory infection.